Enfermedad catastrófica y su incidencia en el estado emocional de una adulta mayor de 80 años de edad en la cuidad de Echeandia - Melendez Morales, Eddison Marcelo (2021)
This research work or case study is focused on catastrophic disease and its incidence on the emotional state of an older person, starting with the definition of catastrophic disease tells us that it deteriorates the health of human beings due to its high level of complexity, tends to produce disability in patients, in this research was developed on the types of diabetes, specifically type 2 diabetes that older adults have, it tells us that this type of diabetes is a chronic pathology since it does not allow Our body uses insulin properly, therefore it does not allow it to maintain glucose in the bloodstream at stable levels, this disease at the same time can manifest itself with depressive episodes, anxiety, insomnia and irritability or also present stress due to learning to manage this disease every day. The treatment based on cognitive behavioral therapy for depression with the application of the technique of retribution, dominance and liking was achieved to improve their lifestyle, their state of mind, communication with their daughter, family life. The diagnosis is made through the interview and observation, using in this way the medical history, psychometric tests and the geriatric depression scale - Yesavage Test. This case study was carried out in Echeandía, Bolívar province, the cognitive-behavioral approach was applied and had the collaboration of the older adult and her daughter.